Terminal Archive? Taking and Returning Sound recordings: Two Examples from the Vienna Phonogrammarchiv - Lechleitner, Gerda (European Journal of Musicology, 2022)
An overall assumption might express that music in general and songs in particular belong to the performers – researchers are interested in any music and “take” songs or instrumental pieces (as sound recordings) with them, often also to an archive. Metaphorically speaking, the sounds of a region leave their original place, captured by interested persons, enthusiasts or researchers, to be then studied, listened to and stored elsewhere. The stories behind the recorded music will be shown. Unequal recording situations give rise to recordings of different content and context – in that respect, the moving around of what was recorded where and by whom will be retraced from early expeditions showing a “standard” field research situation, in contrast to an “exceptional” research situation as conducted in prisoner-of-war camps during WWI. Two examples, a recording of instrumental music performed by a Crimean Tatar and a well-known story spoken in a special South Italian dialect, underline the process of taking and returning sound recordings. Finally, the discussion is related to what happened with the music and what the role of the performer or the source community, researcher and archivist is. What are the consequences of their relationship with each other?